The advantage of global fitting of data involving complex linked reactions - Herman, Petr; Lee, J Ching (Methods in molecular biology, 2012)
In this chapter, we demonstrate the advantage of the simultaneous multicurve nonlinear least-squares analysis over that of the conventional single-curve analysis. Fitting results are subjected to thorough Monte Carlo analysis for rigorous assessment of confidence intervals and parameter correlations. The comparison is performed on a practical example of simulated steady-state reaction kinetics complemented with isothermal calorimetry (ITC) data resembling allosteric behavior of rabbit muscle pyruvate kinase (RMPK). Global analysis improves accuracy and confidence limits of model parameters. Cross-correlation between parameters is also reduced with accompanying enhancement of the model-testing power. This becomes especially important for validation of models with "difficult" highly cross-correlated parameters. We show how proper experimental design and critical evaluation of data can improve the chance of differentiating models.
Keywords: pyruvátkinasa; kalorimetrie; Calorimetry; Rabbits; Animals; Pyruvate Kinase; Monte Carlo Method; králíci; metoda nejmenších čtverců; zvířata; Least-Squares Analysis; metoda Monte Carlo